Impact of first-birth career interruption on earnings: Evidence from administrative data - Julie. L Hotchkiss; M. Melinda Pitts; Mary Beth Walker (Federal Reserve Bank of Atlanta, 2014)
This paper uses unique administrative data to expand the understanding of the role women's intermittency decisions play in the determination of their wages. We demonstrate that treating intermittency as exogenous significantly overstates its impact. The intermittency penalty also increases in the education level of the woman. The penalty for a woman with a high school degree with an average amount of intermittency during six years after giving birth to her first child is roughly half the penalty for a college graduate. We also demonstrate the value of using an index to capture multiple dimensions of the intermittency experience, and we illustrate the importance of firm dynamics in the determination of a woman's wage.
Keywords: J13; J31; J22; 330; intermittency; administrative data; career interruptions; fertility; labor supply; wage differentials